Gerontographics and consumer behavior in later life: Insights from the life course paradigm. Issue 1 (2nd January 2020) - Moschis, George P.; Mathur, Anil; Sthienrapapayut, Thuckavadee
ABSTRACT: The present article applies the life course paradigm to the study of older consumers. It is based on the general life course premise that events experienced in later life in the form of biophysical, social, and psychological changes create demand for readjustment and adaptation to new life conditions that define the multi-dimensional processes of aging and influence consumer behavior. These aging processes are collectively integrated into a model to develop stages of aging, known as "gerontographics, " that people go through in later life. To test the model's efficacy in predicting consumption-related activities, a convenience sample ( N  = 383) of adults aged 45 and older is used to develop the gerontographics model and compared it to commonly used measures of aging (chronological and cognitive age) in predicting select consumer behaviors relevant to people in later life. The results reveal the value of the gerontographics model in understanding and explaining the consumer behavior of older adults. Implications of these findings and directions for further research are also discussed.